The depth of tumor hierarchy and its impact on hypertumor susceptibility - Jibeom Choi; Suhyeon Kim; Sunmi Lee; Junpyo Park (Scientific Reports)
Abstract Cancer cells, despite their shared origin, could be heterogeneous with respect to their stemness, plasticity, self-renewal, and oncogenicity. Recent findings indicate that a small proportion of the cancer cells oligopolize the capacity to produce diverse cancer subtypes and metastasize to other sites. Analogous to the apical hierarchy observed in adult stem cells, such versatile cancer cells were termed cancer stem cells. Meanwhile, hypertumors that exploit the cooperation of other cancer cells may disrupt the integrity of the tumor, prompting tumor regression. The biology of cancer stem cells and hypertumors has substantial clinical potential, but no study up to date has investigated the effect of cancer hierarchy on hypertumor progression. In this study, we developed biologically relevant models that elucidate the dynamics of hypertumor progression under different hierarchical structures. Our models align with previously observed data from human breast cancer subpopulations capable of state transitions. We tested and compared the progression dynamics of cancer clusters with different characteristics. Considering the trade-off between proliferation and mutation risk, our computational results suggest that existence of the cancer stem cells with high self-renewal and replication could be the prerequisite for attaining larger cancer size. In contrast, if a small cancer size is sufficient to induce lethality, a tumor composed of homogeneous cells would take less time to reach such a threshold size. Consequently, the hierarchical structure of cancer that reaches a lethal size may vary across species, representing a relevant mechanism of Peto’s paradox. The formulations presented in this study link the less attended aspects of cancer which would provide integrative insights for therapeutic strategies.